Microbial manganese(III) reduction fuelled by anaerobic acetate oxidation - Szeinbaum, Nadia (Environ Microbiol, 2017)
Soluble manganese in the intermediate 1III oxidation state (Mn(3+)) is a newly identified oxidant in anoxic environments, whereas acetate is a naturally abundant substrate that fuels microbial activity. Microbial populations coupling anaerobic acetate oxidation to Mn(3+) reduction, however, have yet to be identified. We isolated a Shewanella strain capable of oxidizing acetate anaerobically with Mn(31) as the electron acceptor, and confirmed this phenotype in other strains. This metabolic connection between acetate and soluble Mn(3+) represents a new biogeochemical link between carbon and manganese cycles. Genomic analyses uncovered four distinct genes that allow for pathway variations in the complete dehydrogenase-driven TCA cycle that could support anaerobic acetate oxidation coupled to metal reduction in Shewanella and other Gammaproteobacteria. An oxygen-tolerant TCA cycle supporting anaerobic manganese reduction is thus a new connection in the manganese-driven carbon cycle, and a new variable for models that use manganese as a proxy to infer oxygenation events on early Earth.